Problems of improving the structure of GDP economy and the distribution of the tax burden in the Republic of Armenia - Kirakosyan, Gevorg (Bulletin of Yerevan University G: Economics, 2021)
The article analyzes the issues of mutual influence of the sectoral structure of the economy and the distribution of the tax burden. The changes in the sectoral structure of the gross domestic product in the Republic of Armenia, the dynamics of economic growth and their impact on the tax/GDP ratio were considered. The negative impact of  non-taxable sectors of the economy on uneven distribution of the tax burden  is substantiated. Possible ways to change the structure of economic growth in Armenia were suggested in terms of both improving its quality and increasing the tax/GDP indicator.
Keywords: gross domestic product; tax burden; tax policy; economic growth; structural changes in the economy